Reliability and validity of Stroke specific quality of life Urdu version - A preliminary approach - Sidra Hanif, Hafsah Arshad, Kinza Anwar, Hafsah Gul Khattak (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To measure reliability, validity, and psychometric properties of Urdu version of Stroke-Specific Quality of Life scale. Methodology: A longitudinal cross-sectional observational survey was conducted from March 2019 to February 2020. The sample size was calculated by using Rao soft and non-probability convenient sampling technique was used to raise the sample. For translation purpose, the original English version of SSQOL was translated into Urdu by National Language Promotion Department, Govt. of Pakistan.96 stroke survivors filled the final SSQOL Urdu version twice within seven-day period. Data was analyzed by using Spearman and Pearson correlation, Cronbach’s alpha, Intra-class Correlation Coefficient (ICC) at their threshold values, independent t-test, and One-way ANOVA at p < 0.05. Results: The SSQOL-U exhibited acceptable to excellent internal consistency with Cronbach’s alpha= 0.943 with ICC= 0.84-0.93. In comparison ceilings effects were higher than floor effects. Results also established high test-retest reliability in all domains had Spearman’s rho scores >0.8 except for Energy, family, and Mood. An acceptable item to scale correlation convergent validity with rp values ranged between 0.81–0.97. Practical Implication: The SSQOL-U will be utilized by practitioners and researchers across the country to accurately measure patient reported quality of life in post stroke patients. Conclusion: SS-QOL-U showed adequate psychometric properties. SS-QOL-U was found reliable and valid tool to measure the quality of life in Urdu-speaking patients having subacute and chronic stroke. Key words: Stroke, validity, reliability, Stroke specific quality of life